Psychosis associated to CASPR2 autoantibodies and ovarian teratoma: A case report. (March 2020) - Herrmann, Matthias L.; Bruchner, Niklas; Martin, Pascal; Wildgruber, Dirk
Highlights: First report of CASPR2 associated psychosis related to an ovarian teratoma. Prompt reduction of psychotic symptoms after excision of teratoma. The diagnosis of autoimmune psychosis can be made in the presence of autoantibodies in the serum while CSF is unremarkable. Patients with depressive and psychotic symptoms non-responding to antidepressant and antipsychotic treatment should be screened for neuronal autoantibodies including CASPR2.